A self-emulsifying formulation of Sonchus oleraceus Linn for an improved anti-diabetic effect in vivo. Issue 2 (7th February 2020) - Chen, Lei; Lin, Xiujun; Fan, Xiaoyun; Lv, Qiyan; Fang, Huan; Chenchen, Yaqiong; Teng, Hui
Abstract : The aim of the present study was to develop a self-emulsifying drug delivery system (SEDDS) containing the extract of S oleraceus Linn (SOL) with improved intestinal stability in order to increase oral bio-potency. Abstract : The aim of the present study was to develop a self-emulsifying drug delivery system (SEDDS) containing the extract of S oleraceus Linn (SOL) with improved intestinal stability in order to increase oral bio-potency. SOL was effectively incorporated into emulsions, which showed resistance to in vitro digestion without any destruction of its phenolic acids, glycosides and aglycone. SEDDS and SOL were also prepared for the comparison of in vivo anti-diabetic effects. Four weeks of daily treatments of SEDDS dramatically improved the quality of life for diabetic rats. Streptozotocin (STZ) caused body weight reduction, which was reversed by SEDDS at a low dose (100 mg kg −1 ), and it was more effective than SOL at a high dose (200 mg kg −1 ). SEDDS also improved the response to glucose tolerance, which was significantly higher than that of SOL. On the basis of these findings, the SEDDS approach might be an efficacious dosage option to enhance the nutraceutical properties of SOL.